Genomics and Development of Lentinus tigrinus: A White-Rot Wood-Decaying Mushroom with Dimorphic Fruiting Bodies. (6th November 2018) - Wu, Baojun; Xu, Zhangyi; Knudson, Alicia; Carlson, Alexis; Chen, Naiyao; Kovaka, Sam; LaButti, Kurt; Lipzen, Anna; Pennachio, Christa; Riley, Robert; Schakwitz, Wendy; Umezawa, Kiwamu; et al.
Abstract: Lentinus tigrinus is a species of wood-decaying fungi (Polyporales) that has an agaricoid form (a gilled mushroom) and a secotioid form (puffball-like, with enclosed spore-bearing structures). Previous studies suggested that the secotioid form is conferred by a recessive allele of a single locus. We sequenced the genomes of one agaricoid ( Aga ) strain and one secotioid ( Sec ) strain (39.53–39.88 Mb, with 15, 581–15, 380 genes, respectively). We mated the Sec and Aga monokaryons, genotyped the progeny, and performed bulked segregant analysis (BSA). We also fruited three Sec/Sec and three Aga/Aga dikaryons, and sampled transcriptomes at four developmental stages. Using BSA, we identified 105 top candidate genes with nonsynonymous SNPs that cosegregate with fruiting body phenotype. Transcriptome analyses of Sec/Sec versus Aga/Aga dikaryons identified 907 differentially expressed genes (DEGs) along four developmental stages. On the basis of BSA and DEGs, the top 25 candidate genes related to fruiting body development span 1.5 Mb (4% of the genome), possibly on a single chromosome, although the precise locus that controls the secotioid phenotype is unresolved. The top candidates include genes encoding a cytochrome P450 and an ATP-dependent RNA helicase, which may play a role in development, based on studies in other fungi.